The Portuguese version of the Basic Empathy Scale (BES): Dimensionality and measurement invariance in a community adolescent sample - Anastácio, Susana (2016)
Empathy is the heightened ability to cognitively perceive and/or affectively share the emotions of others, which has been consistently associated with desirable social interactions. This paper aimed to test the bi-factorial structure of a Portuguese version of the Basic Empathy Scale and examine its variation by gender and age using a large community sample (n=1029) of adolescents. The two-factor model, originally developed and supported by other cross-cultural validations, presented good fit indicators which was similar across genders and adolescent age groups. Girls were more empathic than boys and younger adolescents were more empathic than the older ones. Further support for the validity of the new scale comes from its relations to measures of social skills and aggression which were similar to theoretical predictions. In conclusion, the Portuguese version of the BES is a consistent and valid instrument for the assessment of empathy in samples of adolescents aged 12 to 18 years old in Portugal, which can now be used in cross-cultural studies of this important psychological construct.